Respuesta :

Answer:

9x is the answer

Step-by-step explanation:

-x-(-10x)

-x+10x

9x

[tex]\huge\text{Hey there!}[/tex]

[tex]\huge\text{-x - (-10x)}[/tex]

[tex]\huge\text{= -1x - (-10x)}[/tex]

[tex]\huge\text{= -1x + 10x}[/tex]

[tex]\huge\textsf{COMBINE the LIKE TERMS}[/tex]

[tex]\huge\text{= (-1x + 10x)}[/tex]

[tex]\huge\text{= 9x}[/tex]

[tex]\huge\text{Answer: \textsf{9x}}[/tex]

[tex]\huge\text{Good luck on your assignment \& enjoy your day!}[/tex]

~[tex]\frak{Amphitrite1040:)}[/tex]